High-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead and bismuth corrosion and preparation method of high-strength oxide dispersion strengthened FeCrAl alloy
By introducing Y-Zr-O nano-strengthening phase into ODS FeCrAl alloy, a dense alumina film is formed, which solves the problem of the alloy being susceptible to corrosion in the lead-bismuth cold fast reactor environment, and achieves the excellent corrosion resistance and mechanical strength of liquid lead-bismuth at high temperatures.
Patent Information
- Application Number
- CN202510049236.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
ODS FeCrAl alloys are susceptible to erosion and dissolution of liquid lead-bismuth in lead-bismuth cold fast reactor environment, resulting in material failure, and the prior art is difficult to effectively prevent such corrosion.
By introducing Y-Zr-O nanostrengthening phase into FeCrAl alloy, a dense alumina film is preferred to form, which prevents the erosion of lead-bismuth melt from the alloy matrix, and controls the precipitation ratio of the nanostrengthening phase by regulating the oxygen content and the amount of ball mill powder, and improves the corrosion resistance of the alloy.
The excellent corrosion resistance of ODS FeCrAl alloy to liquid lead-bismuth at high temperatures is achieved, which enhances the mechanical strength and corrosion resistance of the alloy and extends the service life of the material.
Smart Images

Figure CN119876771A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of corrosion-resistant nuclear materials, and in particular to a high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion and a preparation method thereof. Background Art
[0002] Oxide dispersion strengthened (ODS) FeCrAl alloys have excellent mechanical properties and radiation swelling resistance due to the dispersed nano-scale oxide particles in the matrix pinning dislocations and grain boundaries, capturing dislocated atoms and helium bubbles generated by irradiation, etc., making them candidate materials for advanced nuclear reactor cladding and structural materials. On the basis of good processing and forming, the Al content (≥4wt%) in the matrix provides sufficient element supply for the ODS FeCrAl alloys to form a protective alumina film under high-temperature air, supercritical water and high-temperature and high-pressure steam conditions, achieving compatibility of high-temperature strength, radiation resistance and corrosion resistance. However, the lead (bismuth) cooled fast reactor, one of the fourth-generation advanced reactors, uses liquid lead (bismuth) alloy as coolant. The high-density lead-bismuth alloy has unique erosion, dissolution and oxidation effects on the cladding and structural materials. While the lead-bismuth melt diffuses inward along the grain boundaries, the Ni and Fe elements in the structural materials are gradually dissolved, resulting in material failure. Although it has been proven that aluminum oxide can be generated on the surface of ODS FeCrAl alloy, due to the strong penetration and strong corrosiveness of lead-bismuth alloy, iron-rich and chromium-rich multilayer oxides are more likely to be generated on the alloy surface, such as patent CN117385353 A. When in service for a long time, the multilayer oxides may peel off due to interface stress, and the material has the risk of re-corrosion. Summary of the invention
[0003] The purpose of the present invention is to provide a high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion and a preparation method thereof. The method can be used to preferentially disperse and precipitate high-density, fine-sized Y-Zr-O nano-strengthening phase in the FeCrAl alloy matrix instead of slightly coarse-sized Y-Al-O phase nano-particles, and combined with sufficient Al content, promote the formation of a dense aluminum oxide film on the alloy surface, so that the bottom matrix is protected from lead-bismuth alloy corrosion, and achieve the ODS FeCrAl alloy used in lead-cooled fast reactors with excellent high-temperature mechanical strength and corrosion resistance.
[0004] The technical solution involved in the present invention is as follows:
[0005] A high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion, the chemical composition of the alloy is as follows by mass percentage:
[0006] C≤0.01%, Cr: 11~25%, Al: 5.0~10.0%, W: 0~3.0%, Ta+V≤0.35%, Zr: 0.1~0.5%, Y: 0.1~0.5%, O: 0.15~0.5%, Fe is the balance.
[0007] The high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion preferably has the following chemical composition, measured by mass percentage:
[0008] C: 0.001~0.006%, Cr: 14~20%, Al: 6.0~8.0%, W: 0.5~2.0%, Ta+V≤0.15%, Zr: 0.2~0.35%, Y: 0.2~0.35%, O: 0.2~0.4%, Fe is the balance.
[0009] The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion has a microstructure consisting of a body-centered cubic matrix of FeCrAl, and Y-Zr-O phases and Y-Al-O phase nanoparticles dispersed and precipitated at high density in the matrix.
[0010] The high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion has a Y-Zr-O phase of cubic YZrO3 and trigonal Y4Zr3O 12 Nanoparticles, the Y-Al-O phase is Y4Al2O9 nanoparticles with a monoclinic structure; the precipitation of Y-Zr-O phase nanoparticles reduces the average particle size of the total nano-reinforced phase to below 8nm, significantly improving the mechanical strength of the oxide dispersion-strengthened FeCrAl alloy.
[0011] In the high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion, the volume ratio of Y-Zr-O phase and Y-Al-O phase nanoparticles in the total precipitated phase is controlled by the O content of the alloy, and the volume ratio of Y-Zr-O phase nanoparticles is greater than 60%.
[0012] The high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion has an excess O content of >0.1wt% in the oxide dispersion-strengthened FeCrAl alloy, where the excess O content = alloy O content - O content introduced by Y2O3 powder.
[0013] The high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion has a tensile rate of ≤1×10 -3 s -1 Under the conditions of 550℃ tensile yield strength>400MPa, tensile strength>550MPa, and elongation>20%.
[0014] The high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion is immersed in a liquid lead-bismuth melt at saturated oxygen concentration and 550° C., and a dense aluminum oxide film is formed on the surface.
[0015] The method for preparing the high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion comprises the following steps:
[0016] (1) According to the alloy composition, FeCrAl pre-alloy powder is prepared by atomization using an atomization powder making device;
[0017] (2) After the pre-alloyed powder and the oxide powder are mixed, they are ball-milled under the protection of high-purity Ar gas to obtain mechanically alloyed powder;
[0018] (3) After the ball-milled alloy powder is vacuum packaged, hot isostatic pressing solidification treatment, forging treatment and final annealing treatment are performed to obtain the high-strength oxide dispersion strengthened FeCrAl alloy.
[0019] The method for preparing a high-strength oxide dispersion-strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion comprises the following steps: the oxide powder used for mixing is one or more of iron oxide, chromium oxide, aluminum oxide, zirconium oxide and yttrium oxide, and the element content and oxygen content of the matrix of the oxide dispersion-strengthened FeCrAl alloy are jointly controlled by controlling the dosage of the single or mixed oxide powder.
[0020] The design concept of the present invention is:
[0021] The characteristic that the Y-Zr-phase is more likely to combine with O-vacancies than the Y-Al-phase in the ball milling process is utilized to promote the preferential nucleation of Y-Zr-O phase nanoparticles with small sizes to replace Y-Al-O phase nanoparticles; the characteristic that the precipitation ratio of the Y-Zr-O phase and the Y-Al-O phase can be controlled by the alloy O content or / and the excess O content, and the nano-reinforced phase is promoted to be composed of a high-density Y-Zr-O phase by increasing the O content of the powder and the subsequent alloy, thereby increasing the strength of the ODS FeCrAl alloy; the characteristic that the Al of the alloy matrix can quickly diffuse outward under high temperature conditions and combine with external oxygen is utilized to promote the rapid formation of a dense aluminum oxide film on the surface of the ODS FeCrAl alloy in a lead-bismuth environment, thereby preventing the lead-bismuth melt from further corroding the alloy matrix, thereby improving the high-temperature lead-bismuth corrosion resistance of the alloy.
[0022] The addition of Zr may have a negative impact on the formation of aluminum oxide film in FeCrAl alloys. However, by increasing the O content, more Y-Zr-O phase nanoparticles are promoted to precipitate before Y-Al-O phase nanoparticles, and the Zr element is concentrated in the form of YZrO3 and Y4Zr3O 12The second phase is consumed in the form of nanoparticles, reducing the residual Zr element in the matrix and its influence on the formation of alumina film, thereby achieving multi-faceted improvements in the machinability, mechanical strength and corrosion resistance of the ODSFeCrAl alloy.
[0023] The advantages and beneficial effects of the present invention are:
[0024] 1) The present invention promotes the nucleation of Y-Zr-O phase nanoclusters in FeCrAl ball-milled powder by adding Zr element, and disperses and precipitates smaller Y-Zr-O phase nanoparticles in the heat-cured alloy, thereby obtaining an ODS FeCrAl alloy with improved strength.
[0025] 2) The present invention provides a preparation method that can achieve simultaneous enhancement of the mechanical strength and lead-bismuth corrosion resistance of the ODS FeCrAl alloy, and effectively control the oxygen content in the ODS alloy by adjusting the content of the mixed oxide powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope image of the nano-reinforced phase distribution in the hot isostatically pressed ODS FeCrAl alloy of Example 1.
[0027] Figure 2 This is a particle size distribution diagram of the nano-reinforced phase in the hot isostatically pressed ODS FeCrAl alloy of Example 1.
[0028] Figure 3 This is a high-resolution transmission electron microscope image of the nano-reinforced phase in the hot isostatically pressed ODS FeCrAl alloy of Example 1.
[0029] Figure 4 This is a fast Fourier transform diagram of the nano-strengthening phase in the hot isostatically pressed ODS FeCrAl alloy of Example 1.
[0030] Figure 5 The tensile curves of the ODS FeCrAl alloy at 550°C after forging deformation and heat treatment at 1000°C for 1 hour in Example 2 and the ODS FeCrAl alloy without Zr element are shown in the figure. The results of two sets of parallel samples of the tensile test are shown in the figure, 1-1 and 1-2 are the tensile curves of Example 2 after forging deformation and heat treatment at 1000°C for 1 hour; 2-1 and 2-2 are the tensile curves of the ODS FeCrAl without Zr element after forging deformation and heat treatment at 1000°C for 1 hour.
[0031] Figure 6 This is a scanning electron microscope (SEM) image of the cross-sectional morphology of the hot isostatically pressed ODS FeCrAl alloy in Example 1 after the lead-bismuth corrosion test at 550°C for 1000 hours.
[0032] Figure 7 This is a SEM image of the surface morphology of the hot isostatically pressed ODS FeCrAl alloy in Example 1 after the lead-bismuth corrosion test at 550°C for 1000 hours.
[0033] Figure 8 This is a SEM photograph of the cross-sectional morphology of the annealed ODS FeCrAl alloy after the lead-bismuth corrosion test at 550°C for 2000 hours in Example 2.
[0034] Fig. 9 The cross-sectional morphology (left) and the analysis results of the elements Al, O, Fe, and Pb by energy dispersive spectroscopy (EDS) line scan (right) of the annealed ODS FeCrAl alloy after the lead-bismuth corrosion test at 550°C for 2000 hours in Example 2. DETAILED DESCRIPTION
[0035] In order to make the technical solution of the present invention clear and obvious to those skilled in the art, the present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to these embodiments.
[0036] Unless otherwise specified, the purity of various alloy element raw materials used in the present invention is higher than 99.95wt%, and the volume purity of high-purity Ar gas is 99.999%.
[0037] Example 1
[0038] In this embodiment, the composition (mass percentage) of the high-strength ODS FeCrAl alloy resistant to liquid lead-bismuth corrosion is Fe-18.0Cr-6.0Al-2.0W-0.1Ta-0.35Zr-0.25Y2O3-0.2O. The specific preparation process steps are as follows:
[0039] According to the alloy ratio, a pre-alloyed powder with a composition of Fe-18.0Cr-6.0Al-1.0W-0.1Ta-0.35Zr-0.2Y was prepared by atomization. After mixing 2 kg of pre-alloyed powder with a size less than 150μm with 6.4 grams of alumina powder with a size of 50nm, a high-energy ball mill was used to perform ball milling under the protection of high-purity Ar gas to achieve mechanical alloying of the FeCrAl powder. After powder vacuum packaging, hot isostatic pressing and peeling treatment, Fe-18.0Cr-6.0Al-2.0W-0.1Ta-0.35Zr-0.25Y2O3-0.2O hot isostatic pressed alloy was obtained. TEM microstructure observation was performed on it, and the distribution of the obtained nano-oxides was as follows Figure 1 As shown in Figure 1, the fine-sized nano-oxides are evenly distributed in the alloy matrix. Figure 2 As shown, the particle size of the nano-reinforced phase was calculated using Nanomeasurer software. Figure 2The size distribution results show that the oxide size is mainly concentrated in the range of 4 to 10 nm, making the average particle size no more than 7 nm. The composition of the nano-oxides was analyzed using high-resolution TEM and Fourier transform diffraction spots. In addition to the generation of a small amount of Y-Al-O phase nanoparticles (volume ratio of about 20%), such as Figure 3-Figure 4 As shown, fine, cubic YZrO3 particles are also generated in the alloy and have a good coherence relationship with the alloy matrix, indicating that Y-Zr-O phase nanoparticles are dispersed and precipitated in the ODS FeCrAl alloy matrix and play a role in reducing the average particle size of nano-oxides.
[0040] Example 2
[0041] In this embodiment, the composition (mass percentage) of the high-strength ODS FeCrAl alloy resistant to liquid lead-bismuth corrosion is Fe-14.0Cr-7.0Al-1.0W-0.1V-0.3Zr-0.4Y2O3-0.3O. The specific preparation process steps are as follows:
[0042] According to the alloy ratio, a pre-alloyed powder with a composition of Fe-14.0Cr-7.0Al-1.0W-0.1V-0.3Zr was prepared by atomization. 1 kg of pre-alloyed powder with a size less than 150μm was mixed with 4.0 grams of Y2O3 powder with a size of 30-50nm and 3.5 grams of chromium oxide powder with a size of 5μm, and the mechanical alloying of FeCrAl powder was completed by ball milling under the protection of high-purity Ar gas using a high-energy ball milling device. After powder vacuum packaging, hot isostatic pressing and peeling treatment, Fe-14.0Cr-7.0Al-1.0W-0.1V-0.3Zr-0.4Y2O3-0.3O alloy was obtained. TEM microstructure observation was performed on it, and the fine-sized nano-oxides were evenly distributed in the alloy matrix. The nano-oxides were mainly composed of Y4Zr3O with a volume ratio of about 52%. 12 , YZrO3 with a volume ratio of about 44%, and Y4Al2O9 nanoparticles with a volume ratio of about 4%. The average particle size is reduced to below 6nm, so that the nano-reinforced phase maintains a good coherent relationship with the alloy matrix.
[0043] Then, the obtained alloy was hot forged and room temperature forged to obtain a rod with a diameter of 13 mm, and finally heat treated at 1000°C for 1 h to carry out high temperature mechanical property tests. Figure 5 As shown, at a stretching rate of 1.2×10 -4 s -1Under the conditions of 550°C tensile results, it can be seen that compared with the performance of ODS FeCrAl alloy with similar alloy composition but without Zr element added, the increase in yield strength and tensile strength of the ODS alloy in Example 2 exceeds 30%, and the combination of Zr and O elements significantly improves the mechanical properties of the alloy at 550°C.
[0044] Example 3
[0045] In this embodiment, the hot isostatically pressed alloy in Example 1 was used to conduct a 550°C lead-bismuth corrosion test. The specific experimental steps are as follows: the reactor containing the lead-bismuth alloy is heated to about 200°C, the lid of the reactor is opened, and the hot isostatically pressed ODS FeCrAl alloy sample of Example 1 is placed in the reactor. After the lid of the reactor is closed, the temperature is raised to 550°C, and the temperature of the reactor is kept constant. After the alloy sample is soaked for 1000 hours, the reactor begins to cool down. When the temperature drops to 200°C, the lid of the reactor is opened to take out the sample, and after cooling in air, a cross-sectional SEM observation is performed. The results are as follows: Figure 6 As shown, it can be seen that there is no multilayer oxidation product on the alloy surface, the alloy grain boundary is not corroded by lead and bismuth, and the sample is intact. The residual lead-bismuth alloy on the alloy surface was washed away using a mixed solution of CH3COOH+H2O2+C2H5OH with a volume ratio of 1:1:1, and the surface was observed by SEM. The results are shown in Figure 7 As shown in the figure, there is no flocculent, needle-shaped, flaky, or regional oxidation product on the alloy surface, and the alloy matrix morphology is clearly visible. EDS component analysis shows that there is a slight enrichment of aluminum oxide on the alloy surface, indicating that a thin aluminum oxide film is formed on the alloy surface. This thin aluminum oxide film effectively blocks the corrosion of the lead-bismuth melt on the matrix elements and prevents the lead-bismuth alloy from penetrating into the matrix.
[0046] Example 4
[0047] In this example, the annealed alloy of Example 2 was used to conduct a 550°C lead-bismuth corrosion test. The specific experimental steps are as follows: the reactor containing the lead-bismuth alloy was heated to about 200°C, the lid of the reactor was opened, the ODS FeCrAl alloy sample of Example 2 was placed in the reactor, and the lid of the reactor was closed and the temperature was raised to 550°C. After 3000 hours of corrosion at 550°C, the sample was taken out, cooled in air, and then a cross-sectional SEM observation was performed. The results are shown in FIG. Figure 8 As shown in the figure, a thin oxide film on the surface effectively blocks the corrosion of the lead-bismuth melt on the alloy matrix. EDS line scanning analysis is performed on it. Fig. 9 The results show that there is a significant enrichment of Al and O concentrations at the interface between FeCrAl alloy and lead-bismuth alloy, indicating that the oxidation product on the alloy surface is an aluminum oxide film. ODS FeCrAl alloy simultaneously achieves excellent high-temperature mechanical properties and high-temperature lead-bismuth corrosion resistance.
[0048] The implementation results show that the material of the present invention promotes the preferential precipitation of fine Y-Zr-O phase nanoparticles replacing slightly larger Y-Al-O phase nanoparticles by adding an appropriate amount of Zr element, thereby improving the mechanical strength of the ODS FeCrAl alloy. In view of the potential hazard of the Zr element in the lead-bismuth environment that may hinder the formation of alumina film on the surface of the ODS FeCrAl alloy, by regulating the ball-milled powder and the O content of the alloy, a large amount of Zr elements are consumed in the form of Y-Zr-O strengthening phase, reducing the Zr content of the alloy matrix, reducing and eliminating the adverse effects on the formation of protective alumina film, and obtaining an ODS FeCrAl alloy with both excellent lead-bismuth corrosion resistance and excellent high-temperature mechanical properties.
[0049] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to allow researchers familiar with this technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion, characterized in that: The chemical composition of the alloy is as follows by mass percentage: C≤0.01%, Cr: 11~25%, Al: 5.0~10.0%, W: 0~3.0%, Ta+V≤0.35%, Zr: 0.1~0.5%, Y: 0.1~0.5%, O: 0.15~0.5%, Fe is the balance.
2. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 1, characterized in that: Preferably, the chemical composition of the alloy is as follows by mass percentage: C: 0.001~0.006%, Cr: 14~20%, Al: 6.0~8.0%, W: 0.5~2.0%, Ta+V≤0.15%, Zr: 0.2~0.35%, Y: 0.2~0.35%, O: 0.2~0.4%, Fe is the balance.
3. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 1 or 2, characterized in that: The microstructure of oxide dispersion strengthened FeCrAl alloy consists of body-centered cubic matrix of FeCrAl, high-density dispersed Y-Zr-O phase and Y-Al-O phase nanoparticles in the matrix.
4. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 3, characterized in that: The Y-Zr-O phase is cubic YZrO3 and trigonal Y4Zr3O 12 Nanoparticles, the Y-Al-O phase is Y4Al2O9 nanoparticles with a monoclinic structure; the precipitation of Y-Zr-O phase nanoparticles reduces the average particle size of the total nano-reinforced phase to below 8nm, significantly improving the mechanical strength of the oxide dispersion-strengthened FeCrAl alloy.
5. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 3, characterized in that: The volume ratio of Y-Zr-O phase and Y-Al-O phase nanoparticles in the total precipitated phase is controlled by the O content of the alloy, and the volume ratio of Y-Zr-O phase nanoparticles is >60%.
6. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 1 or 2, characterized in that: The excess O content of the oxide dispersion strengthened FeCrAl alloy is >0.1wt%, and the excess O content = the alloy O content - the O content introduced by the Y2O3 powder.
7. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 1 or 2, characterized in that: At a stretching rate of ≤1×10 -3 s -1 Under the conditions of 550℃ tensile yield strength>400MPa, tensile strength>550MPa, and elongation>20%.
8. The high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 1 or 2, characterized in that: The alloy is immersed in liquid lead-bismuth melt at 550°C and saturated oxygen concentration, and a dense aluminum oxide film is formed on the surface.
9. A method for preparing a high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to any one of claims 1 to 8, characterized in that: The steps include: (1) According to the alloy composition, FeCrAl pre-alloy powder is prepared by atomization using an atomization powder making device; (2) After the pre-alloyed powder and the oxide powder are mixed, they are ball-milled under the protection of high-purity Ar gas to obtain mechanically alloyed powder; (3) After the ball-milled alloy powder is vacuum packaged, hot isostatic pressing solidification treatment, forging treatment and final annealing treatment are performed to obtain the high-strength oxide dispersion strengthened FeCrAl alloy.
10. The method for preparing a high-strength oxide dispersion strengthened FeCrAl alloy resistant to liquid lead-bismuth corrosion according to claim 9, characterized in that: The oxide powder used for mixing is one or more of iron oxide, chromium oxide, aluminum oxide, zirconium oxide and yttrium oxide. By controlling the dosage of single or mixed oxide powder, the element content and oxygen content of the oxide dispersion strengthened FeCrAl alloy matrix can be jointly controlled.
Citation Information
Cited By
Corrosion-resistant cladding coating and preparation method thereof
CN120556024A
Accident-resistant fuel rod cladding coating and manufacturing method thereof
CN121565515A